2022
DOI: 10.3390/su14031706
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Waste Recycling: The Mechanical Performance of Concrete Based on Limestone and Plastic Waste

Abstract: Recycling is among the best management strategies to avoid dispersion of several types of wastes in the environment. Research in recycling strategies is gaining increased importance in view of Circular Economy principles. The exploitation of waste, or byproducts, as alternative aggregate in concrete, results in a reduction in the exploitation of scarce natural resources. On the other hand, a productive use of waste leads to a reduction in the landfilling of waste material through the transformation of waste in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Simultaneously, as compared to concrete made with traditional aggregates, concrete containing flexible aggregates may display more ductile behavior, resulting in enhanced behavior in crack development and propagation. Recycled plastic may repair and overlay damaged cement-based concrete surfaces in pavements, bridges, floors, and dams [5].…”
Section: Literature Review 21 Management Of Plastic Wastesmentioning
confidence: 99%
“…Simultaneously, as compared to concrete made with traditional aggregates, concrete containing flexible aggregates may display more ductile behavior, resulting in enhanced behavior in crack development and propagation. Recycled plastic may repair and overlay damaged cement-based concrete surfaces in pavements, bridges, floors, and dams [5].…”
Section: Literature Review 21 Management Of Plastic Wastesmentioning
confidence: 99%
“…At present, the reasonable dosage of limestone powder in concrete is generally no more than 15% [20], which greatly limits the utilization rate of limestone powder. As a result, several researchers [21,22] suggested creating ternary or multicomponent cementing materials by combining limestone powder with additional mineral admixtures, providing a great idea. Lima-Guerra et al [23] succeeded in producing concrete by mixing limestone powder with bentonite.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary cementitious materials containing silica-rich components, for example, silica fume (SF) [10,11], fly ash (FA) [12,13], rice husk ash (RHA) [14] and blast furnace slag (BFS) [13,15,16], are by-product pozzolans. Other forms of SCs include recycled aggregate [17][18][19][20][21], waste foundry sand [22], tire rubber [23,24], ceramic [25], granite powder (GP) [26][27][28][29], glass sands [21], limestone powder (LP) [30][31][32], and red mud (RM) [33][34][35]. Furthermore, waste steel (WS) [36], plastic [37], cotton [38], and carpet fibers [39] have been added to concrete mixes to increase the resistance of concrete under tensile cracking.…”
Section: Introductionmentioning
confidence: 99%
“…The tests showed that including up to 15% FGWP into geopolymer concrete (GPC) improved mechanical strength and durability. Ferrotto et al [31] looked into ways to utilize concrete as a waste container, concentrating on waste from limestone quarries and taking on the difficulty of incorporating plastic waste into typical concrete mixtures. The mechanical properties of concrete combined using extra alternative aggregates categorized as waste were researched and addressed in this study to demonstrate the potential of achieving this goal with satisfactory performance loss.…”
Section: Introductionmentioning
confidence: 99%